2018
DOI: 10.3390/app8040479
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of a Three-Dimensional Asymmetric Multi-Storey Reinforced Concrete Structure

Abstract: Featured Application: Authors are encouraged to provide a concise description of the specific application or a potential application of the work. This section is not mandatory.Abstract: This study discusses the seismic behavior of a geometrically asymmetric three-storey reinforced concrete (RC) building, considering torsional effect and material nonlinearity. The building is a test structure that was used for seismic performance evaluation in the SMART 2013 (Seismic design and best-estimate Methods Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In literature, there are some articles that analyse the seismic response of both symmetric and asymmetric multi-storey reinforced concrete structures [4][5][6]. Dimova and Alashki show in [4] that even the symmetric reinforced concrete structures behave under seismic loading like the irregular ones under accidental small eccentricity, and the method for the correction of the structure response is presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there are some articles that analyse the seismic response of both symmetric and asymmetric multi-storey reinforced concrete structures [4][5][6]. Dimova and Alashki show in [4] that even the symmetric reinforced concrete structures behave under seismic loading like the irregular ones under accidental small eccentricity, and the method for the correction of the structure response is presented.…”
Section: Introductionmentioning
confidence: 99%
“…By using the finite element model of asymmetric three-storey reinforced concrete building, validated by modal experiments under low-intensity ground motion simulation, it is shown that the torsional effects are much greater for an asymmetric structure than for a symmetric structure with approximately the same design conditions, especially under high-intensity earthquakes [5].…”
Section: Introductionmentioning
confidence: 99%
“…The modern seismic design provisions for reinforced concrete (RC) structures enforce ductility requirements to meet target limit states, avoiding brittle failure [1]. As a typical shear failure of an RC member is often very brittle, more accurate descriptions of shear behavior are imperative in achieving proper safety goals.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic performance of frame structures has been continually investigated by researchers, mainly through developing structures with maximum energy dissipation capacity [1][2][3][4][5][6][7][8][9]. In the 1950s, a new type of frame structure with a soft first story was designed by pioneers such as Le Corbusier [10] who applied the soft-first-story idea by lifting the structure off the ground.…”
Section: Introductionmentioning
confidence: 99%